PENGARUH BUDAYA ORGANISASI, DISIPLIN KERJA DAN KOMITMEN TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA MEDAN KOTA - Ida Sari; Anton A.P. Sinaga; Erwin Pardede (JURNAL PROINTEGRITA, 2021)
Many factors affect performance, including organizational culture, commitment, work discipline, leadership, compensation, and so on. However, the factors studied are organizational culture, work discipline and commitment. This study aims at finding the effect of organizational culture and work discipline and commitment simultaneously to the performance of employees at the Medan Kota Primary Tax Office. The population of this research is 116 employees. In determining the sample, the Slovin formual was used and 54 people are obtained. The data collection techniques of this research are questionnaires and documentation study while the data analysis technique uses the classical assumption test, multiple regression, t test, F test and the coefficient of determination. The results showed that organizational culture showed a significant influence on the performance of employees at the Medan Kota Primary Tax Office. The better the organizational culture, the higher the performance. Work discipline shows a significant influence on the performance of employees at the Medan Kota Pratama Tax Office. The better the work discipline variable, the higher the performance variable. Commitment shows a significant effect on the performance of employees at the Medan Kota Pratama Tax Office. The better the commitment, the higher the performance. Simultaneously there is a significant influence on the influence of organizational culture, work discipline, and commitment to employee performance.